Amazing Grace - Hoffman, Mary, 1945-; Binch, Caroline (New York : Dial Books for Young Readers, 1991)
Although a classmate says that she cannot play Peter Pan in the school play because she is African-American, Grace discovers that she can do anything she sets her mind to do.
Sequel: Boundless Grace.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal starred, October 1991.
Book Links (A.L.A.), November 1999.
Publisher's Weekly, October 2009.
Keywords: African Americans -- Fiction; Identity -- Fiction; Theater -- Fiction; Individuality -- Fiction